Optimization of the cytokine secretion assay for human IL‐2 in single and combination assays. (28th April 2015) - Deng, Nan; Mosmann, Tim R.
Abstract The cytokine secretion assay identifies live cytokine‐secreting cells by capturing the secreted cytokine on a surface‐bound capture antibody in dilute suspension culture, followed by detection with a fluorescent anti‐cytokine antibody. However, examining the kinetics of cytokine detection revealed that IL‐2 staining reached a maximum at early times and then declined, whereas staining for other cytokines including interferon (IFNγ) increased for up to 90 min. The decline in IL‐2 staining could have been due to rapid cessation of cytokine synthesis, coupled with internalization of cytokine/antibody complexes from the cell surface. Consistent with this model, addition of the anti‐IL‐2 detection antibody during the cytokine secretion step resulted in higher and more sustained staining. This modified method enhanced staining of IL‐2 and IL‐4, but not IFNγ, tumor necrosis factor alpha (TNFα), or IL‐5. However, the longer secretion times possible in the modified assay also improved detection of other cytokines in multi‐cytokine combinations. © 2015 International Society for Advancement of Cytometry